Gallium incorporation in InAlN: role of the chamber design and history, and the effects of growth pressure. Issue 4 (11th November 2016) - Ben Ammar, H.; Minj, A.; Gamarra, P.; Lacam, C.; Tordjman, M.; di Forte‐Poisson, M. A.; Morales, M.; Chauvat, M. P.; Ruterana, P.
Abstract : In this work, we have investigated the non‐intentional incorporation of gallium in InAlN layers grown by metal organic vapor phase epitaxy (MOVPE) using two reactors. Atomic force microscopy (AFM) and electron dispersive X‐ray spectroscopy (EDS) have been used to characterize the surface morphology and the atomic composition of InAl(Ga)N/GaN structures. The horizontal chamber systematical produces pure ternary layers whereas the close coupled shower head vertical chamber can lead to quaternary alloys. Cleaning the latter significantly reduces the amount of gallium to 1% in the epilayers. Moreover, we show an alternative way to reduce the amount gallium: the use of an intermediate growth pressure typically around 80 Torr drops the inclusion of gallium to 6%. In the presence of such amount of Ga, the growth process appears to be modified and there is a competition between In and Ga for their incorporation, and the Al composition is systematically reduced. The morphology of the layers is also observed to suffer, with the formation of large and closed trenches toward a possible three dimensional growth mode when the layer thickness is increased.